Promoting Asia-Pacific economic cooperation : perspectives from East Asia - Deng, Yong, 1966- (Macmillan, 1997)
Informed by international regime theory, this book probes into the distinctive process of regional cooperation in Asia-Pacific by focusing on the roles and perspectives of China, Japan and Southeast Asian states. It challenges some of the conventional wisdom on international cooperation and sheds new light on the evolution of the regional and global political economic order in the post-hegemonic era.